'The language is disgusting and they refer to my disability': the cyberharassment of disabled people. Issue 8 (13th September 2016) - Alhaboby, Zhraa A.; al-Khateeb, Haider M.; Barnes, James; Short, Emma
Abstract: Disabled people face hostility and harassment in their socio-cultural environment. The use of electronic communications creates an online context that further reshapes this discrimination. We explored the experiences of 19 disabled victims of cyberharassment. Five themes emerged from the study: disability and health consequences, family involvement, misrepresentation of self, perceived complexity, and lack of awareness and expertise. Cyberharassment incidents against disabled people were influenced by the pre-existing impairment, perceived hate-targeting, and perpetrators faking disability to get closer to victims online. Our findings highlight a growing issue requiring action and proper support.